The caregiver burden and the psychosocial adjustment of caregivers of cardiac failure patients - Filiz Dirikkan; Leyla Baysan Arabacı; Ece Mutlu (Türk Kardiyoloji Derneği Arşivi, 2018)
Objective: This cross-sectional, descriptive study evaluated the relationship between the caregiver burden and the psychosocial adjustment of caregivers to cardiac failure patients. Methods: Between November 18, 2015 and March 1, 2016, a preliminary information form, the Caregiver Burden Scale, and the Psychosocial Adjustment to Illness Scale were used to assess the caregivers of 200 patients being treated in the cardiology service of a university hospital. Results: Among the caregivers, 75% were primary or secondary school graduates, 36% were housewives, and 43% were the patients' spouse. Of the group, 71% had been caring for the patients for 5 years or less. The caregivers described cardiac failure as 'difficulty with inhalation, fatigue, asthenia, insomnia, and swelling in the hands and feet.' They reported feelings of sorrow, fear, despair, bewilderment, anger, and guilt when they learned about the diagnosis, and they indicated that they generally managed those feelings by themselves. A total of 94% of the caregivers remarked that after the diagnosis they experienced physical, psychological, social, occupational, or economic changes. Of the respondents,74% felt sad and adversely affected, 71.5% faced difficulties with care provision, and 84% felt anxiety about the possibility of losing the patient while under their care, the disease prognosis, surgery (pacemaker implantation), and adjustment to the treatment. The study participants' caregiver burden and psychosocial adjustment scale scores were below average. There were moderate statistically significant relationships between 3 subdimensions of the caregiver burden and psychosocial adjustment to illness scales (p<0.05). Conclusion: The participating caregivers of cardiac failure patients described moderate difficulties due to caregiving and adjusting to the illness. It was determined that as the distress felt due to caregiving increased, psychosocial adjustment to illness deteriorated.